Severely high serum unbound bilirubin level after abdominal surgery in a newborn. Issue 3 (18th June 2013) - Morioka, Ichiro; Miwa, Akihiro; Yokota, Tomoyuki; Huu, Chuong Thieu Do; Nagasaka, Miwako; Koda, Tsubasa; Matsuo, Kiyomi; Morikawa, Satoru; Shibata, Akio; Hisamatsu, Chieko; Nishio, Hisahide; Yamada, Hideto; et al.
Abstract We report a newborn with intestinal malrotation who developed a severely high serum unbound bilirubin level and a low serum albumin level without a marked increase in serum total bilirubin level after abdominal surgery, which required exchange transfusion and albumin supplementation. The serum unbound bilirubin level may be highly relative to the serum total bilirubin level in newborns who have undergone abdominal surgery soon after birth and are hypoalbuminemic after surgery.